NEW TECHNOLOGY AND ETHICAL HUMAN RESOURCE MANAGEMENT - Ogunyemi, Kemi (European Scientific Journal, ESJ, 2014)
With technological progress, temporal and spatial firm boundaries are changing and a new institutional form is emerging from redefinitions of working hours and workspace. Many of these changes are positive (Hitt, 1999; Afuah, 2003). However, there are some issues of unfairness to employees. Employers seek new ways to squeeze more ‘performance’ from the same employees, especially given recent challenges to global and local economies. Sometimes, the redefining of boundaries is unilateral. Employees may be harmed, perhaps even without either party taking full cognizance. As says Akerlof (1980), society sometimes can adopt even practices that have no benefit and are detrimental to its members. This conceptual paper raises ethical considerations for human resource policy development and practice in the light of specific instances of technological progress. There is a need to ensure that today’s employee does not end up back in the iron cage (DiMaggio and Powell, 1983), and a need to take into consideration the costs to people (negative externalities affecting work-life balance, quality of life, family time, societal impact, stress and anxiety levels, illness and deaths; etc.). Socially responsible management also entails being careful not to end up legitimizing unethical or unfair practice which others may thoughtlessly copy (DiMaggio and Powell, 1983; Deephouse, 1996). A convenience sample of senior managers attending an executive programme at Lagos Business School confirmed that there are indeed challenges and illustrate the effect of new technology on employee personal time and space autonomy (Cozzetto and Pedeliski, 1997) and on physical and psychological stress levels.